Optical filter for providing the required illumination to enable narrow band imaging - Silva, Manuel Fernando Ribeiro (2014)
This paper presents the design, fabrication and characterization of two Fabry Perot type optical filters (415 nm and 540 nm) for enabling Narrow Band Imaging (NBI) in medical devices (MD). The two-colour illumination should satisfy a highly specific optical design, which is composed of a thin-film optical filter stack of titanium dioxide (TiO2 ) and silicon dioxide (SiO2 ) thin-films and commercially available light-emitting diodes (LEDs). The short-wavelength design is the most critical and simulations show a maximum relative optical output of 21 % at 415 nm with Full-Width-Half-Maximum (FWHM) of 13 nm for a blue LED with the designed optical filter, which is confirmed by experiment. The green light simulations show a maximum relative optical output of 34 % with FWHM 36 nm at 540 nm. The TiO2 and SiO2 thin films were fully characterized.